Abnormal gut microbiota composition is associated with experimental autoimmune prostatitis‐induced depressive‐like behaviors in mice. Issue 9 (7th April 2020) - Du, He‐Xi; Liu, Yi; Zhang, Li‐Gang; Zhan, Chang‐Sheng; Chen, Jing; Zhang, Meng; Chen, Xian‐Guo; Zhang, Li; Liang, Chao‐Zhao
Abstract: Background: Depressive symptoms are found in approximately 78% of chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) patients, but the pathological mechanisms remain unknown. Increasing evidence suggests that abnormal gut microbiota may play an important role in depression. Thus, we aimed to investigate whether gut microbiota contributes to CP/CPPS‐associated depression by using a mouse model of experimental autoimmune prostatitis (EAP). Methods: Male nonobese diabetic mice were immunized twice by subcutaneous injection of prostate antigen and adjuvant. Behavioral tests consisted of an open field test, sucrose preference test, forced swimming tests, and tail suspension test was used to confirm the depression‐like symptoms that were induced by EAP. Then, fecal samples were collected, and 16S ribosomal RNA gene sequencing was performed to detect differences in gut microbiota composition between control and EAP group. Additionally, fecal bacteria from the control and EAP mice were transplanted into antibiotics‐induced pseudo‐germ‐free mice to investigate the effects on host behaviors and the composition of gut bacteria. Results: EAP was successfully established and exhibited depressive‐like behaviors in mice. The 16S rRNA analysis of fecal samples indicated the abnormal composition of gut microbiota in the EAP mice compared to the control mice. In the fecal microbiota transplant study, antibiotics‐treated pseudo‐germ‐free mice presented depressive states as compared to naïve mice. Fecal bacteria transplant from EAP mice, but not from control mice, into the pseudo‐germ‐free mice, significantly exaggerated host depression‐like behaviors. Moreover, fecal bacteria transplants from control and EAP mice induced distinct alterations in α‐diversity and β‐diversity indices. In all, 24 bacteria at six phylogenetic levels were remarkably changed by the fecal bacteria transplantation. Conclusions: Abnormal gut microbiota composition after EAP induction may contribute to the development of depression in mice. A therapeutic strategy that targets gut microbiota may provide an alternative treatment for alleviating this condition.